Geotechnical Parameters Determination by Using Seismic Refraction Tomography in The New Capital City of Indonesia, Nusantara: Implication to Analysis of Soil Compaction - Handoyo, Handoyo; Amalia, Atika; Sigalingging, Asido Saputra; Ruchimat, Acep; Wiyono, Wiyono; Akin, Özgenç (Geological Agency, 2025)
The new capital city of Indonesia, Nusantara, in East Kalimantan, is undergoing enormous infrastructural development in Indonesia. Understanding the condition of the soil, sediment, and hardrock layers at this location is critical for geotechnical working principles. In this study, the first arrival P-wave tomography method was used to determine the distribution of P-wave velocity and geotechnical parameters (e.g. porosity, density, void ratio) to better understand the condition of the rock layers at this location. This study involved the use of seismic refraction tomography data consisting of forty-eight channels with a distance between geophones of 1 m, and a source in the form of a sledgehammer weighing 3 kg with a separation distance of 3 m. The natural frequency of the geophones used was 4.5 Hz with a recording time of 1.0 sec. Results of this investigation reveal a thinning hardrock layer from the south to the north, with a thickness ranging from 7 to 16 m correlated to consolidated alluvium. Moreover, the geotechnical parameter of sediment layers, top soil (clayey soil) and unconsolidated alluvium, has a density value range from 1.6 to 1.8 g/cm³, porosity 0.31 to 0.38, and void ratio 0.44 to 0.59. These findings show that the soil layer in the south to the middle of line profile of the studied area has low to medium compaction, requiring soil hardening activities (mechanical compaction) for infrastructure construction. Finally, the findings of this study are expected to help with infrastructure development in the IKN by utilizing geophysical technique.